Congenital malformations in infants conceived following assisted reproductive technology in comparison with spontaneously conceived infants. (19th March 2013) - Farhi, A.; Reichman, B.; Boyko, V.; Mashiach, S.; Hourvitz, A.; Margalioth, E. J.; Levran, D.; Calderon, I.; Orvieto, R.; Ellenbogen, A.; Meyerovitch, J.; Ron-El, R.; et al.
Abstract: Objective : To evaluate the risk for congenital malformations diagnosed at birth following assisted reproductive technology (ART) treatments compared with live births conceived spontaneously. Methods : A retrospective cohort study including 9042 live births following ART and 213 288 spontaneously conceived (SC) live births during the period 1997–2004.The cohort was linked to the national live birth registry to determine the outcome of the pregnancies including congenital malformations. Results : An increased adjusted risk for all congenital malformations was observed in ART compared with SC infants [2.4% versus 1.9%; ORadj = 1.45; 95% CI: 1.26, 1.68]. The increased risk was observed in singleton births [2.4% versus 1.8%; ORadj = 1.41; 95% CI: 1.14, 1.71] but not in the ART conceived multiple births [2.5% versus 2.6%.; ORadj = 1.15; 95% CI: 0.90, 1.46]. Significantly increased adjusted risks for nervous, circulatory, digestive and genital system malformations were evident in the ART singleton group compared to SC infants. In addition, increased risks were also observed in separate comparisons of IVF births versus SC [ORadj = 1.28; 95% CI: 1.00, 1.63] and ICSI births versus SC [ORadj = 1.56; 95% CI: 1.31, 1.84]. Data regarding pregnancy termination or congenital malformation diagnosed later in life were not included. Conclusion : Infants born following ART were at significantly increased risk for congenital malformations compared to live birth conceived spontaneously.